National museums in Africa : identity, history and politics - Silverman, Raymond Aaron; Abungu, George; Probst, Peter (Abingdon, Oxon ; New York, NY : Routledge, 2022)
"National Museums in Africa brings the voices of African museum professionals into dialogue with scholars and, by so doing, is able to consider the state of African national museums from fresh perspectives. Covering all regions of the continent, the volume's thirteen chapters allow for a deep and nuanced understanding of the intricate interplay between past and present in contemporary Africa. Taking stock of the shifting museum landscape in Africa, with new players like China and South Korea challenging the conditions of cultural exchange, the book demonstrates that national museums are being rediscovered as important sites of political engagement and cultural negotiation. This is the first book to critically examine the roles national museums in Africa have played in the societies in which they are situated, but it is also the first to consider the roles that national museums might play in current debates concerning the restitution and repatriation of cultural patrimony taken from Africa during the colonial era. Informed by a comparative and interdisciplinary perspective, this ground-breaking book will appeal to anyone interested in museums in Africa. It will be particularly useful to scholars and students working in the areas of museum and heritage studies, African studies, anthropology, archaeology, history, art history and cultural studies"--
OCLC-licensed vendor bibliographic record.
Keywords: National museums -- Africa; Museums -- Political aspects -- Africa -- History; Museums -- Social aspects -- Africa -- History; HISTORY / Africa / General